2018
DOI: 10.1590/2177-6709.23.1.097-107.bbo
|View full text |Cite
|
Sign up to set email alerts
|

Tooth transposition: a multidisciplinary approach

Abstract: Tooth transposition is one of the most difficult dental anomalies to treat in the dental clinic. Several factors must be taken into account with a view of making the best decision. The aim of this study was to discuss treatment modalities for tooth transposition, their advantages and disadvantages. Additionally, it aims at presenting a clinical case of transposition between canine and lateral incisor in the upper quadrant on the right side. The treatment of choice was extraction of one transposed tooth. A mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…In the literature survey performed during this study, 12 articles reported an association between TT and agenesis 3,4,9,11,13,14,17,20,54,55,62,64 but none described the occurrence of tooth giroversion. The reported frequency of the association between TT and agenesis in previous studies was around 37-40% 16,65 . In addition, retained canine was one of the most common dental anomalies found in combination with TT (Table 1), and this may suggest a common etiological origin for these conditions.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In the literature survey performed during this study, 12 articles reported an association between TT and agenesis 3,4,9,11,13,14,17,20,54,55,62,64 but none described the occurrence of tooth giroversion. The reported frequency of the association between TT and agenesis in previous studies was around 37-40% 16,65 . In addition, retained canine was one of the most common dental anomalies found in combination with TT (Table 1), and this may suggest a common etiological origin for these conditions.…”
Section: Discussionmentioning
confidence: 88%
“…TT can occur at any age and is usually diagnosed during clinical and radiographic examination, prior to orthodontic treatment. The distribution of TT cases by sex varies according to the geographical location 1,65,66 . It can affect the maxillary or mandibular dentition, unilaterally or bilaterally 66 .…”
Section: Introductionmentioning
confidence: 99%
“…Radiologic examination complements clinical examination by demonstrating complete dental inversion in the case of total transposition, tooth overlap, or root inversion in partial transposition. 28 The most frequent tooth diagnosed with dental transposition is the maxillary canine that can change its place with the lateral incisor or first premolar (►Fig. 5).…”
Section: Anomalies Of Dental Structure Anomalies In Positionmentioning
confidence: 99%
“…When the affected teeth are completely transposed, complete transposition is observed. If the roots remain in a normal position with only transposed crowns, incomplete transposition is defined [ 13 ]. Tooth agenesis is most commonly observed in patients with CLCP [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%